Analisis Pengaruh Profitabilitas, Kebijakan Dividen, Kebiijakan Hutang, Kepemilikan Manajerial, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Astriningsih, Novia, Drs. Agus Endro S, M.Si (2016)
The aim of this study was to determine the effect of profitability, dividend policy, debt policy, managerial ownership, and the size of the company on firm value. The company's value in this study is proxied by Price Book Value (PBV). Population of this research are manufacturing companies listed in Indonesia Stock Exchange in 2011-2014. Samples were taken by using purposive sampling technique and the total sample of 64 companies for four years in accordance with the criteria. Analysis techniques using classic assumption test and multiple regression analysis. Based on the research results in the regression model in mind a few things, as follows: (1) variable profitability significantly influence the value of the company, (2) a variable dividend policy significantly influence the value of the company, (3) variable debt policy has no effect no significant effect on the value of the company, (4) variable managerial ownership has no effect no significant effect on the value of the company, (5) variable size companies have a significant effect on firm value. Keywords: profitability, dividend policy, debt policy, managerial ownership, the size of the company, the company's value